Therapeutic Drug Monitoring of Asparaginase Activity-Method Comparison of MAAT and AHA Test Used in the International AIEOP-BFM ALL 2009 Trial - Lanvers-Kaminsky, Claudia; Rüffer, Andrea; Würthwein, Gudrun; Gerss, Joachim; Zucchetti, Massimo; Ballerini, Andrea; Attarbaschi, Andishe; Smisek, Petr; Nath, Christa; Lee, Samiuela; Elitzur, Sara; Zimmermann, Martin; et al. (Therapeutic drug monitoring, 2018)
BACKGROUND: In the international AIEOP-BFM ALL 2009 trial, asparaginase (ASE) activity was monitored after each dose of pegylated Escherichia coli ASE (PEG-ASE). Two methods were used: the aspartic acid β-hydroxamate (AHA) test and medac asparaginase activity test (MAAT). As the latter method overestimates PEG-ASE activity because it calibrates using E. coli ASE, method comparison was performed using samples from the AIEOP-BFM ALL 2009 trial. METHODS: PEG-ASE activities were determined using MAAT and AHA test in 2 sets of samples (first set: 630 samples and second set: 91 samples). Bland-Altman analysis was performed on ratios between MAAT and AHA tests. The mean difference between both methods, limits of agreement, and 95% confidence intervals were calculated and compared for all samples and samples grouped according to the calibration ranges of the MAAT and the AHA test. RESULTS: PEG-ASE activity determined using the MAAT was significantly higher than when determined using the AHA test (P < 0.001; Wilcoxon signed-rank test). Within the calibration range of the MAAT (30-600 U/L), PEG-ASE activities determined using the MAAT were on average 23% higher than PEG-ASE activities determined using the AHA test. This complies with the mean difference reported in the MAAT manual. With PEG-ASE activities >600 U/L, the discrepancies between MAAT and AHA test increased. Above the calibration range of the MAAT (>600 U/L) and the AHA test (>1000 U/L), a mean difference of 42% was determined. Because more than 70% of samples had PEG-ASE activities >600 U/L and required additional sample dilution, an overall mean difference of 37% was calculated for all samples (37% for the first and 34% for the second set). CONCLUSIONS: Comparison of the MAAT and AHA test for PEG-ASE activity confirmed a mean difference of 23% between MAAT and AHA test for PEG-ASE activities between 30 and 600 U/L. The discrepancy increased in samples with >600 U/L PEG-ASE activity, which will be especially relevant when evaluating high PEG-ASE activities in relation to toxicity, efficacy, and population pharmacokinetics.
Keywords: polyethylenglykoly; monitorování léčiv; protinádorové látky; Enzyme Assays; asparaginasa; Antineoplastic Agents; Drug Monitoring; lidé; enzymatické testy; Humans; Polyethylene Glycols; Asparaginase